Molecular Interactions between Thiostrepton and the TipAS Protein from Streptomyces lividans. Issue 5 (24th February 2014) - Myers, Cullen L.; Harris, Jesse; Yeung, Jacky C. K.; Honek, John F.
Abstract In Streptomyces lividans, the expression of several proteins is stimulated by the thiopeptide antibiotic thiostrepton. Two of these, TipAL and TipAS, autoregulate their expression after covalently binding to thiostrepton; this irreversibly sequesters the antibiotic and desensitizes the organism to its effects. In this work, additional molecular recognition interactions involved in this critical event were explored by utilizing various thiostrepton analogues and several site‐directed mutants of the TipAS antibiotic binding protein. Dissociation constants for several thiostrepton analogues ranged from 0.19 to 12.95 μM, depending on the analogue. The contributions of specific structural elements of the thiostrepton molecule to this interaction have been discerned, and an unusual covalent modification between the antibiotic and a new residue in a TipAS mutant has been detected.